Stress-strain analysis of pipelines laid in permafrost; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Burkov P. V. Petr Vladimirovich (Latest Technology in Oil-and-Gas Pipelines and Petroleum Storage, 2016)
Title screen